SCIENTIFIC AND PRACTICAL FOUNDATIONS FOR USING INTERNATIONAL BRAILLE GRAPHIC STANDARDS IN THE CREATION OF TACTILE ATLASES AND UNLABELED (CONTOUR) MAPS FOR STUDENTS WITH VISUAL IMPAIRMENTS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article provides an in-depth analysis of the scientific and practical foundations for using international Braille graphic standards in the development of tactile atlases and contour maps for students with visual impairments. The necessity of systematizing tactile symbols, global experience, and established standards is examined. Special attention is given to BANA, ISO, and GOST R standards, their functions, advantages, and research-proven effectiveness. The relevance of adapting international standards to the conditions of Uzbekistan without developing a separate national standard is substantiated.